Bentuk Pelibatan Masyarakat Dalam Melakukan Pengawasan Terhadap Pelaksanaan Pemilihan Bupati dan Wakil Bupati - Aksah Kasim; Andi Heridah (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
Analyze and look for forms of community participation in effective supervision of the Election of Regents and Deputy Regents. The research method used is normative legal research. The results showed that the form of community involvement in supervising the Election of Regents and Deputy Regents, including the indicators for Monitoring the Permanent Voter List (DPT) in the Election of Regents and Deputy Regents of Barru Regency was considered effective, because the dominant respondents who stated that they were very effective and effective were 53 respondents (70.67 %), then who stated that it was less effective and ineffective only 22 respondents (29.33%), the indicator of understanding political education was considered ineffective, because only 23 respondents (30.67%), who stated very effective and stated effective, while 52 respondents stated that it had not been effective and ineffective, and the Ambassador Monitoring Indicator had not been implemented properly and effectively by the Supervisory Committee for the Election of the Regent and Deputy Regent of Barru Regency, because there were still more dominant respondents who stated that it was less effective and ineffective. as many as 46 respondents (61.33%), while only 29 respondents (38.67%), and the K . Indicator The cooperation between supervisors and monitors in the election of the Regent and Deputy Regent of Barru Regency is also considered ineffective, because as many as 41 respondents (54.67%) stated that it was not effective and ineffective, while only 34 respondents stated that it was very effective and effective (45.33%).